Case Report: Transformation of Visual Snow Syndrome From Episodic to Chronic Associated With Acute Cerebellar Infarct - Puledda, Francesca; Villar-Martínez, María Dolores; Goadsby, Peter J. (Frontiers in Neurology, 2022)
Visual snow syndrome is a novel neurological condition characterized by a panfield visual disturbance associated with several additional symptoms. Although it is usually a continuous and primary disorder, cases of intermittent visual snow have been described in the literature, as well as rare secondary forms. This report is the first description of a case of intermittent visual snow syndrome, which transformed into a persistent form following a posterior circulation stroke due to vertebral artery dissection. At 1 and 2 years after experiencing the acute cerebellar infarct, the patient's only neurological sequalae was visual snow. This case provides a description of how visual snow syndrome may be caused by an underlying brain disorder, and highlights the importance of the cerebellum in the pathophysiology of this relatively unknown condition. It further shows evidence of how existing predispositions might be relevant to the development of visual snow, in certain subjects and following specific circumstances.